From Grammar to Meaning : The Spontaneous Logicality of Language - Caponigro, Ivano; Cecchetto, Carlo (Cambridge : Cambridge University Press, 2013)
In recent years, the study of formal semantics and formal pragmatics has grown tremendously showing that core aspects of language meaning can be explained by a few principles. These principles are grounded in the logic that is behind - and tightly intertwined with - the grammar of human language. In this book, some of the most prominent figures in linguistics, including Noam Chomsky and Barbara H. Partee, offer new insights into the nature of linguistic meaning and pave the way for the further development of formal semantics and formal pragmatics. Each chapter investigates various dimensions in which the logical nature of human language manifests itself within a language and/or across languages. Phenomena like bare plurals, free choice items, scalar implicatures, intervention effects, and logical operators are investigated in depth and at times cross-linguistically and/or experimentally. This volume will be of interest to scholars working within the fields of semantics, pragmatics, language acquisition and psycholinguistics.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Semantics; Grammar, Comparative and general; Meaning (Psychology)